Shigella sonnei: is a change occurring in our middle? - Guevara G., José María (2014)
Objectives: To determine Shigella serogroups as diarrhea etiological agents. Design: Descriptive, retrospective, analytical study. Settomg: Instituto de Medicina Tropical, Universidad Nacional Mayor de San Marcos, Lima, Peru, and Hospital Nacional Daniel A. Carrion, Callao, Peru. Biologic material: Shigella sp. isolates in coprocultures. Interventions: Shigella sp. isolates in coprocultures of outpatient, hospitalized and emergency adult and pediatric patients attended during years 2010 and 2011were reviewed at the hospital WHONET 5.6 database. Shigella were distributed by serogroups. Main outcome measures: Absolute and relative frequency of Shigella sp. Results: Sisty-four Shigellas sp were isolated in 2010; 41 corresponded to flexneri serogroup (64.1%) and 20 to sonnei serogroup (31.3%). Ninety Shigellas sp. were isolated in 2011; 36 corresponded to flexneri serogroup (40%) and 50 to sonnei serogroup (55,6%). Differences were statistically significant. Conclusions: Shigella sonnei was the predominant serogroup at our hospital.